Pengaruh Risiko, Return, dan Perekonomian Indonesia Terhadap Keputusan Berinvestasi Saat Covid-19 - Revo Gilang Firdaus (The Indonesia Capital Market Institute, 2020)
Research on investment decisions when Covid-19 is measured by the influence caused by risk, return, and the Indonesian economy. Respondents were targeted at 20 students with random sampling conducted using a questionnaire. Then the analysis uses SPSS software with validity, reliability, classic assumption, and multiple linear regression tests. The results show that the return variable becomes an influential factor in determining whether to invest in shares when Covid-19 or not. While other independent variables do not affect because they have significance that is not in accordance with the rules. The implications of this research have resulted in encouraging various sectors and parties, such as the government and other involved parties to collaborate with each other and work together to provide education and understanding related to stock investment in students.